Influence of Kenyan Sign Language on Syntactical Patterns of Written English in Primary Schools for the Deaf in Kenya - and Ruth Samoei, C.; Peter Oracha, Adoyo; Edward Kochung, J.; Okutoyi, Joel (2020)
Performance of English in KCPE examination by learners who are deaf has shown a trend of low scores as compared to their hearing counterparts in Nakuru Region. For four consecutive years; 2010, 2011, 2012 & 2013 English mean scores by learners who are deaf in six primary schools in Nakuru region, Kenya were: 29.74, 31.41, 29.58, & 30.27 respectively, while in six selected regular primary schools within the same counties in the respective years, English mean scores were: 48.74, 47.89, 47.87& 56.24. A number of studies have looked at effect of language of instruction and age of onset of hearing loss as variables, yet none considered Effect of Kenya Sign Language (KSL) on written English grammar. The purpose of this study was to analyse the influence of KSL on syntactical patterns of written English written English grammar among learners who are deaf among learners who are deaf in classes five, six and seven in Nakuru Region. Objectives of this study were to: determine influence of KSL on syntactical patterns of written English written English grammar among learners who are deaf in classes five, six and seven. In this study, Language learning was guided by behaviourist theory by who? Descriptive research design was used. Data collected was used to describe nature of existing conditions and relationships. The study was carried out in Nakuru Region, Kenya. Target population comprised 157 learners who are deaf and 21 teachers for English. Saturated sampling technique was used to select 141 learners and 18 teachers. Data was collected using document analysis guide and questionnaire for teachers. Reliability of research instruments with a correlation coefficient(r) of 0.75 was accepted in a pilot study involving 16 learners and 3 teachers, constituting 10% of research population. Face validity of research instruments was established by experts in Department of Special Needs Education of Maseno University. Qualitative data was organised into categories and reported in verbatim as themes and sub-themes emerged. Results from this study established that: learners had difficulties in syntax. OSV word order basic for KSL was evident in students’ written English grammar instead of SVO basic word order for English. This study concluded that KSL had negative impact on syntactical patterns of written English, written English grammar among learners who are deaf among learners who are deaf in classes five, six and seven in Nakuru Region, Kenya. This study recommended use of bilingual approach as a media of instruction to enhance mastery of English grammar for learners who are deaf. Article visualizations: